Fatal Systemic Toxoplasmosis by a Novel Non-archetypal Toxoplasma gondii in a Bryde’s Whale (Balaenoptera edeni) - Díaz-Delgado, Josué; Groch, Kátia R.; Ramos, Hernani G. C.; Colosio, Adriana Castaldo; Alves, Bruna Farias; Pena, Hilda F. J.; Catão-Dias, José L. (Frontiers in Marine Science, 2020)
Toxoplasma gondii is known to cause sporadic clinical disease and fatality in marine mammals worldwide. It has been recognized primarily in odontocetes, pinnipeds, and mustelids; however, there is very limited information available in mysticetes. We report the results of pathological, immunohistochemical, and molecular genotyping analyses in a Bryde’s whale (Balaenoptera edeni) with disseminated toxoplasmosis. A 10.7-m-long, adult, male Bryde’s whale in poor body condition was stranded alive on August 21, 2018 in Pontal do Ipiranga, Linhares, Espirito Santo state (Brazil). The animal died shortly after stranding and was promptly autopsied. The main gross findings were diffuse axial skeletal muscle atrophy, generalized congestion, petechiation and ecchymoses, necrotizing splenitis, hepatitis, myocarditis, pneumonia, and lymphadenitis (prescapular, pulmonary, mediastinal, and mesenteric), bilateral scapulohumeral hemarthros, and severe pulmonary edema. A microscopic examination confirmed the aforementioned diagnoses, featuring a histopathologic signature characterized by multisystemic necrotizing inflammation with vasculitis and disseminated intravascular coagulation, thrombosis, and numerous intralesional protozoal cysts and extracellular tachyzoites morphologically compatible with T. gondii. The immunohistochemical and polymerase chain reaction (PCR) analysis targeting a repetitive 529-bp DNA fragment of T. gondii confirmed toxoplasmosis in the liver, spleen, lung, and lymph nodes. PCR-restriction fragment length polymorphism analysis using 11 markers identified a new non-archetypal genotype, ToxoDB-RFLP genotype #300. Further, the genotyping by microsatellite technique employed 15 markers and confirmed a unique non-archetypal T. gondii strain, designated as PS-TgBaledBrES1. These novel results add to the diversity of this parasite in the world and to the scarce data on T. gondii genotype distribution in cetaceans, representing the first record of toxoplasmosis in a Bryde’s whale and setting the baseline knowledge for future research on T. gondii genotyping research in marine mammals from South America.